PPARδ mediates the effect of dietary fat in promoting colorectal cancer metastasis - Wang, Dingzhi (Cancer Res, 2019)
The nuclear hormone receptor peroxisome proliferator-activated receptor delta (PPARdelta) is a ligand-dependent transcription factor involved in fatty acid metabolism, obesity, wound healing, inflammation, and cancer. Although PPARdelta has been shown to promote intestinal adenoma formation and growth, the molecular mechanisms underlying the contribution of PPARdelta to colorectal cancer (CRC) remain unclear. Here we demonstrate that activation of PPARdelta induces expansion of colonic cancer stem cell (CSC) and promotes CRC liver metastasis by binding to the Nanog promoter and enhancing Nanog expression. Moreover, PPARdelta mediated the effect of a high-fat diet in promoting liver metastasis and induction of colonic CSC expansion. Our findings uncover a novel role of dietary fats in CRC metastasis and reveal novel mechanisms underlying PPARdelta-mediated induction of CSCs and those responsible for the contribution of dietary fats to CRC progression. These findings may provide a rationale for developing PPARdelta antagonists to therapeutically target CSCs in CRC.